Principales métodos de identificación utilizados en odontología forense para el reconocimiento de cadáveres - Bryan Hector, Carguacundo Berrones (2023)
ABSTRACT: Forensic odontology is the science whose main mission is to compile all the information of the stomatognathic system and all the structures that make it up in order to help in the identification of an individual. The present research work has the objective of determining the main methods of identification used in forensic odontology for the recognition of corpses; for this a qualitative, descriptive and bibliographic review study was carried out, considering and analyzing in a rigorously manner approximately 69 bibliographic sources indexed in databases such as Scielo, PubMed, Google Scholar, after being correctly analyzed to obtain a total of 44 reliable bibliographic sources. The results show that various authors point out that forensic odontology is of great importance because it allows, through its methods, the recognition of corpses in which conventional techniques such as dactyloscopy cannot be applied. In turn, they consider the dental clinical history as a primordial document to make a comparison of antemortem and postmortem data. Therefore, it was concluded that this science, in certain situations, becomes the only identification tool, and also allows the recognition of characteristics such as age, sex and race.